STRATEGI DAYA SAING WISATA KOTA TUA JAKARTA - Budisetyorini, Beta; Kandahsari, Dharani; Sarasvati, Ida Ayu Made Paramita (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
The Old City of Jakarta as a major tourist destination, is at the “Competitive Parity” level In the “tourism destination competitiveness” criteria. That position has not been posted in the “Sustained Competitive Advantage” as the highest level. Hence, in order to improve the competitiveness level, the effective and efficient strategy should be formulated and implemented. To formulate the strategy, this research analyse the five components of tourism destination competitiveness by the SWOT analysis model. The five components are Core Resources and Attractors; Supporting Factors and Resources; Destination Management; Destination Policy, Planning and Development and Qualifying and Amplifying Determinants. The SWOT Analysis also includes the SWOT Matrix and Quadran as the reference for formulating the strategy. The result shows that progressive strategy could be formulated and implemented to enhance the competitiveness of the Jakarta Old City.